The Circular Economy Phenomenon Impact on Multinationals Business Model: A Marketing Analysis in the Fashion Industry - Magdalena CIOBANU (Stoian); Angela MADAN (Communications of International Proceedings, 2022)
The latest buzzword—circular economy—has gained traction among academics and practitioners alike. It is the most recent attempt to build a long-term method of integrating economic activity with environmental well-being. The traditional linear economy paradigm continues to dominate business, society, and research. In recent years, the major global polluters (e.g., fashion, oil and gas industries) have faced adversity as a result of business models with significant environmental and social consequences. The demand to reduce the negative effects is set by European practices and regulations - through the circular economy as a step toward carbon neutrality - as well as by consumers. The purpose of this paper is to examine whether multinational corporations have set out to provide solutions to a changing world and the challenges of climate change. This challenge is centered on the energy and fashion industries. The research methodology is exploratory, based on secondary data, and empirical, based on quantitative data collection. This paper is an important research tool, providing a valuable answer to the question of multinational business in a changing economic and environmental context. Taking into account the findings of the literature review as well as the findings of the actual research on circularity practices, the major findings of this paper highlight the transformation process from the linear business model to the value circle. Circularity is expected to become a way of working in the future.
Keywords: sustainability; circular economy; marketing